An Analytical Study of Legal Inference in Shafi'i and Hanafi Schools Regarding Intersex Inheritance Rights - Ahmad Zaki Mubarak (Smart: Journal of Global Islamic Studies and Social Science, 2026)
This study raises the main problem of the determination of Imam Hanafi and Imam Syafi'i regarding the distribution of inheritance rights in this case there is a difference of opinion on Istinbhat Islamic inheritance law through the distribution of inheritance rights. Basically, the determination of gender is an attempt to determine gender with certainty, if it is not possible, then calculate the inheritance portion based on the smallest gender estimate, and the remainder is divided to other heirs. This type of research is library research and the research method used is the normative legal research method with a descriptive analysis research approach and the data analysis technique used in this study uses comparative analysis, namely the analysis of the distribution of inheritance rights Khuntsa Musykil Comparative Study of the Syafii and Hanafi Schools. The results of this study indicate that the views of Imam Hanafi and Imam Syafi'i have similarities and differences in previous Islamic inheritance law When it is not possible to determine clear gender, then the inheritance portion is based on the smallest gender estimate. While Imam Hanafi's application focuses more on the distribution of the smallest portion without too much consideration of gender determination.